Influencers of enhanced performance in agile software development teams - Njomo, Mmadira Elizabeth (My University, 2017)
Due to the trite nature of the software development environment, traditional software methodologies are no longer relied on to deliver software products in a timeous manner. As a response to this limitation, the agile manifesto was launched. The manifesto consists of values and principles centred around the self-organising team’s ability to achieve higher productivity, that is, to deliver software products quickly and with a high quality. With the self-organising team at the centre of this phenomenon, this interpretive case study seeks to gain greater insight into the processes and reasons behind this outcome. The site selected for this study is the IT divisions of a South African bank that have adopted Agile as a methodology to deliver software products. The data was collected through semi structured interviews, focused groups and documentation. The data was analysed qualitatively using thematic and content analysis. The framework for enhanced performance in agile software development teams was conceptualised. The conceptualisation was informed by the empirical evidence and the interpretation of findings and literature
Partial fulfilment of the requirements for the Master in Commerce (Information Systems) (Course work) At the School of Economic and Business Sciences University of the Witwatersrand, 2017
Keywords: Agile software development; Computer software--Development